The use of wood as Smart Building Material = El uso de la madera como Smart Building Material - Cansiong Guerrra, Karen Stephanie; Escobar Avilés, José (Building & Management, 2020)
Abstract One of the materials that plays a paper fundamental in the sector of construction in the wood, because to structure it has excellent properties mechanical that include high strength, good durability, high specific gravity and high moisture content. In the search for new sustainable materials with the environment, there is a need to look for new alternatives and intelligent construction systems, for which smart building materials are used and wood is one of them. The aim is to discover the new intelligent characteristics of wood and its use in construction. In addition to analyzing the progress in his research. Resumen Uno de los materiales que juega un papel fundamental en el sector de la construcción es la madera, pues a nivel estructural tiene excelentes propiedades mecánicas que incluyen sus altos valores de resistencia, durabilidad, peso específico y contenido de humedad. En la búsqueda de nuevos materiales que colaboren con el medio ambiente, existe la necesidad de buscar alternativas y sistemas constructivos con materiales inteligentes y la madera es uno de ellos. El objetivo de este trabajo es descubrir las nuevas características innovadoras de la madera y su uso en el sector de la construcción, además de, analizar los avances en su investigación